Captain America : Sharon Carter. - Lee, Stan, 1922-2018; Kirby, Jack; Waid, Mark, 1962-; Garney, Ron; Brubaker, Ed; DeConnick, Kelly Sue; Simon, Joe (Marvel Worldwide, 2020)
Sharon Carter, the S.H.I.E.L.D. operative known as Agent 13, is one of the world's most capable and determined secret agents! Grandniece of World War II agent Peggy Carter, Sharon proudly upholds her family's fight for truth and justice. Now, thrill to some of her greatest battles! From her first encounter with Captain America as they battle Batroc the leaper, to Sharon's tenure as Director of S.H.I.E.L.D.! But when Cap and Sharon team up to face down Crossbones and Sin, will their long-buried feelings for one another resurface? Plus, Sharon teams with the Black Widow to hunt down a rogue assassin-and defends Avengers Tower from the Absorbing Man!